Neocatechumenal Way: An Example of Controlled Innovation in the Catholic Church - Šantek, Goran Pavel (2003)
The paper focuses on the Neocathecumenal Way, an ecclesiastical movement that arose in 1964, with the purpose of reintegration of the disintegrated symbols of the Spanish Catholics' sacred self.
Projekt MZOS
ENG